The Effect of IFRS 17 Implementation, Auditor Quality, Firm Performance, and Liability Measurement on the Timeliness of Financial Reporting of Insurance Companies During the Transition to IFRS 17 - Nadya Aurelia Khaerani; Lindrianasari Lindrianasari (Lembaga Riset dan Inovasi Al-Matani, 2026)
This study aims to provide empirical evidence on the effect of IFRS 17 implementation, auditor quality, firm performance, and liability measurement on the timeliness of financial reporting in Indonesian insurance companies during the transition period of IFRS 17 adoption. A quantitative panel data approach was employed using data from the annual reports of insurance companies registered with the Financial Services Authority (OJK) in 2023 -2024. The independent variables include IFRS 17 implementation (measured by a dummy variable), auditor quality (Big Four vs. non-Big Four), firm performance (measured by Return on Assets/ROA), and the accuracy of liability measurement between current and previous periods. The dependent variable is the timeliness of financial reporting. The findings are expected to contribute to financial accounting literature and insurance reporting practices under the new accounting standard.